Revisiting gold as a stable, safe haven: Trends, insights, and paths to sustainability - William Ben Gunawan (EcoProfit: Sustainable and Environment Business, 2026)
Background: Gold has long been regarded as a safe haven asset capable of preserving value during periods of financial instability, geopolitical tension, and economic uncertainty. However, recurring global crises, the emergence of alternative assets, and the growing emphasis on sustainability have renewed debates regarding gold’s contemporary relevance and stabilising role. This study aims to revisit and synthesise the scholarly literature on gold as a stable safe haven, with particular attention to its evolving contribution to long-term financial sustainability and systemic resilience. Methods: Employing a mixed-methods design, the study combines bibliometric analysis of Scopus-indexed publications with a qualitative narrative literature review. Bibliometric mapping is used to identify publication trends, influential countries and journals, thematic clusters, and temporal evolution, while the literature review provides in-depth interpretation of dominant findings, methodological approaches, and emerging sustainability perspectives. Findings: The results indicate that gold remains the most consistently studied and empirically supported safe haven asset, particularly during periods of extreme market stress, pandemics, and heightened geopolitical risk. However, its hedging and safe haven properties are shown to be conditional, varying across market regimes, crisis phases, and regional contexts. The literature further suggests that gold’s relevance is increasingly framed within broader sustainability and resilience narratives, emphasising its role in mitigating tail risk rather than delivering constant returns. Conclusion: Overall, the study concludes that gold continues to play a central, albeit conditional, role in enhancing portfolio resilience and financial system stability. These findings contribute to a more nuanced understanding of gold’s function within sustainable finance and offer insights for researchers, investors, and policymakers concerned with long-term economic resilience. Novelty/Originality of this article: This article offers a novel contribution by integrating bibliometric mapping with a comprehensive narrative literature review to systematically trace the evolution of gold safe haven research while explicitly reframing gold’s role within long-term financial sustainability and systemic resilience.